Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Can someone give me a proof or a hint on why the recurrence equation: $$g(k+2)=k*g(k+1)-g(k)$$ has the solution: $$g(k)=c_1 {_0\tilde F_1}(;k;-1)+c_2 Y_{k-1}(2)$$ where ${_0\tilde F_1}(;a;x)$ is the regularized hypergeometric function and $Y_{k-1}(2)$ is the Bessel function of the second kind? Thanks in advance.

share|cite|improve this question
up vote 2 down vote accepted

Your recurrence equation is an instance of the recurrence equation, satisfied by Bessel functions: $$ x J_{\nu-1}(x) + x J_{\nu+1}(x) = 2\nu J_{\nu}(x), \quad x Y_{\nu-1}(x) + x Y_{\nu+1}(x) = 2\nu Y_{\nu}(x) $$ for $x=2$. Moreover, Casoratian of $J_{k-1}(2)$ and $Y_{k-1}(2)$ is non-zero for all $k$ $$ C(J_{k-1}(2), Y_{k-1}(2)) = J_{k-1}(2) Y_k(2) - Y_{k-1}(2) J_k(2) \stackrel{\text{Wronskian}}{=} \left.-\frac{2}{\pi x}\right|_{x=2} = -\frac{1}{\pi} \not= 0 $$ therefore $J_{k-1}(2)$ and $Y_{k-1}(2)$ are linearly independent solutions of the recurrence equation, and hence $g(k) = c_1 J_{k-1}(2) + c_2 Y_{k-1}(2)$ is the fundamental system.

Incidentally: $$ {}_0 \tilde{F}_1\left(;k;-x^2\right) = x^{k-1} J_{k-1}(2x) $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.